Prediction of therapeutic efficacy of gabapentin by Hull Airway Reflux Questionnaire in chronic refractory cough - Mengru Zhang; Qiang Chen; Ran Dong; Li Yu; Zisheng Ai; Xianghuai Xu; Zhongmin Qiu (SAGE Publishing, 2020)
Background: Gabapentin is recommended for the treatment of chronic refractory cough (CRC). This study aims to identify its therapeutic predictors in a prospective clinical study. Methods: A total of 179 patients with CRC were treated with gabapentin. Prior to the therapy, all patients were assessed by Hull Airway Reflux Questionnaire (HARQ) and inhaled capsaicin challenge. When the treatment ended and cough resolution was confirmed, a stepwise logistic regression analysis was performed to identify the therapeutic predictors for gabapentin and to establish the prediction equation. Results: Gabapentin treatment achieved a therapeutic success rate of 66.48%. HARQ scores were significantly higher in responders than non-responders to gabapentin (29.79 ± 9.58 versus 21.95 ± 7.83, t  = -3.685, p  <0.001), which were positively related to the therapeutic efficacy of gabapentin ( r  = 0.433, p  <0.001). The optimal cutoff point of 21.50 in HARQ presented with a moderate ability to predict gabapentin efficacy, with a sensitivity of 84.60% and specificity of 63.60%. Multiple logistic regression identified items of "A tickle in your throat, or a lump in your throat" (OR = 7.927, p  = 0.005), "Cough when you get out of bed in the morning" (OR = 7.016, p  = 0.045), and "Cough with eating" (OR = 6.689, p  = 0.011) as independent predictors. The established logistic regression equation predicted 83.72% of the treatment success rate of gabapentin, which was verified by consequent preliminary revalidating study in 59 patients. Conclusion: HARQ may be useful to screen patients with CRC most likely responsive to gabapentin, and help improve the therapeutic success. Trial registration: http://www.chictr.org/ ; No.: ChiCTR-ONC-13003123